2016
DOI: 10.1002/cpp.2061
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Self‐Blame for the Onset of a Chronic Physical Health Condition and Emotional Distress: A Systematic Literature Review

Abstract: What does this study add? The review presents an exploration of the role of self-blame in emotional adjustment following the diagnosis of a chronic physical health condition. This is the first review to synthesize findings from studies measuring self-blame beliefs directly and specifically for illness onset and their relationship to indicators of distress and wellbeing. Findings suggest that self-blame for illness onset is often associated with emotional distress for people with cancer, HIV/AIDS and cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 112 publications
0
20
0
Order By: Relevance
“…Our metasynthesis showed that important themes raised by the participants, namely acceptance of the condition, increased emotion-regulation skills and reduced feelings of isolation, were only marginally represented in the quantitative outcome measures. Being diagnosed with a long-term physical condition does indeed entail an increased risk for higher depression and anxiety (Clarke & Currie, 2009;Patten, 2001), but it can also involve acceptance of and coping with the condition (Ambrosio et al, 2015), isolation (Ohman, Soderberg, & Lundman, 2003), self-blame (Callebaut, Molyneux, & Alexander, 2017) and emotion-regulation (Wierenga, Lehto, & Given, 2017) and it may be important to measure these outcomes. Furthermore, compassion-based interventions target both mental health difficulties and mental health resources (Bohlmeijer & Westerhof, in press), yet resources such as mental well-being (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our metasynthesis showed that important themes raised by the participants, namely acceptance of the condition, increased emotion-regulation skills and reduced feelings of isolation, were only marginally represented in the quantitative outcome measures. Being diagnosed with a long-term physical condition does indeed entail an increased risk for higher depression and anxiety (Clarke & Currie, 2009;Patten, 2001), but it can also involve acceptance of and coping with the condition (Ambrosio et al, 2015), isolation (Ohman, Soderberg, & Lundman, 2003), self-blame (Callebaut, Molyneux, & Alexander, 2017) and emotion-regulation (Wierenga, Lehto, & Given, 2017) and it may be important to measure these outcomes. Furthermore, compassion-based interventions target both mental health difficulties and mental health resources (Bohlmeijer & Westerhof, in press), yet resources such as mental well-being (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, daily life goes on and basic housing, financial and employment issues and social problems interact with the demands of the illness and may interfere with the capacity for active coping behaviour (Van Houtum, Rijken, & Groenewegen, 2015). In response to the challenges of living with a long-term physical condition, many people report blaming themselves for their perceived role in causing or exacerbating their condition and this self-blame may further increase distress (Callebaut, Molyneux, & Alexander, 2017).…”
mentioning
confidence: 99%
“…Furthermore, patients lacked understanding about the purpose of the tasks and thought it was strange and not credible. In particular, in the domain of somatic diseases, psychosocial treatments offered to alleviate psychosomatic symptoms such as fatigue are known to evoke feelings of self-blame in patients [19]. Taking into account the possible resistance in stakeholders with regard to CBM, it seems essential to involve patients and health care professionals throughout the design process [20].…”
Section: Introductionmentioning
confidence: 99%
“…75,[109][110][111] A further possibility may be the nature of blame, concepts of responsibility and a negative spiral of disempowerment with anxiety. [112][113][114] A different explanation might be a statistical artifact from fallible ascertainment of intent leading to misclassification bias.…”
Section: Researchmentioning
confidence: 99%